Reading "First Alcibiades. An essay on plato’s concept of temperance" - Tomaszewski, Misza (Hybris, 2013)
In this essay I aim to analyse and reconstruct the concept of σωφροσύνη presented in First Alcibiades as well as to place it against the background of the entire Platonic thought related to this term. The problem of „taking care of oneself” (ἐπιμέλεια ἑαυτοῦ) is a central theme in the middle part of the dialogue. Its relation to σωφροσύνη can be presented using the term τέχνη. A man who takes care of himself, takes care of the “place” in a soul related to cognition and thinking. Such type of care is identical with the virtue of “sound mind”. Second key problem is the one of ruling and being ruled by what is appetitive in man. Simple psychology of the author of the dialogue takes the existence of two agonistic elements in the soul: one connected with thinking and one connected with lust. By σωφροσύνη one should understand the mastery of the first over the latter. Identifying two skills — knowing one’s own matters and knowing the matters of the state — with each other makes us interpret σωφροσύνη in such a way that one’s mastery over himself is a condition of his mastery over the others. Simultaneously σωφροσύνη gets very close to the border of being identified with justice (δικαιοσύνη).